148k views
2 votes
NEED HELP ASAP

Question A.) k=5
Question B.) ????

NEED HELP ASAP Question A.) k=5 Question B.) ????-example-1
User Pravs
by
4.5k points

1 Answer

8 votes

Answer:

b)
f^(-1)(x) = (4x+5)/(3)

Explanation:

b) To find the inverse function, switch the
x and
y variables and solve for
y:


f(x) = (3x-5)/(4)\\y = (3x-5)/(4)\\x = (3y-5)/(4)\\4x = 3y-5\\4x+5 = 3y\\(4x+5)/(3) = y\\f^(-1)(x) = (4x+5)/(3)

Verify Answer:


f(1) = (3(1)-5)/(4) = -0.5\\f^(-1)(-0.5) = (4(-0.5)+5)/(3) = 1

User Vortex
by
4.4k points